UPAYA PEMBELAJARAN BACA TULIS QUR’AN DALAM PENINGKATAN KARAKTER SISWA SEKOLAH FULL DAY DI SMPN 1 NGIMBANG LAMONGAN - Salman Zahidi; Ahmad Zhaini (Universitas Islam Lamongan, 2018)
Efforts to improve the quality of education is constantly done, Through the program SMPN 1 Ngimbang, SMPN 1 Ngimbang program is a follow-up of Permendikhud No. 23 of 2014 concerning School Day 8 hours a day for five days, aka full day school. The learning process at SMPN 1 Ngimbangmenggunakan full day system with a good system, it can affect the success of the quality of learning that exist within the institution itself.Thesis entitled